Computer assisted language learning for academic development programmes : an appraisal of needs, resources and approaches - Collett, Philip Godfrey (Rhodes University, Faculty of Education, Department of Education, 1994)
A major objective of Academic Development Programmes is to support the student in acquiring a level of language competence which is sufficient to enable the student to cope with the linguistic demands of academic courses. Language teaching programmes in the Academic Development context in South Africa suffer from a number of constraints: staffing, time on task, relevance, and difficulty of integration with learning in other coUrses. A review of developments in the field of Computer Assisted Language Learning (CALL) shows that computers can be used to support language learning. CALL materials range from simple instructional programs to powerful linguistic research tools and need to be integrated into wider language programmes so as to support and enhance other teaching and learning activities. However, relatively little research has been done to investigate the feasibility and effectiveness of CALL in language development courses within Academic Development programmes in South Africa. The development of a system designed to enable students to practise proof-reading and editing is described and evaluated. Suggestions are made for using this system with other CALL materials within a computer assisted language development environment. It is argued that CALL can be used feasibly and effectively in this environment to enhance learning and to counteract constraints.
Keywords: English language -- Computer-assisted instruction; Language arts -- Computer-assisted instruction; Language acquisition; Computers and literacy; English language -- Study and teaching -- Foreign speakers; Computer-assisted instruction